Pengaruh Segmentasi, Targeting, dan Positioning terhadap Keputusan Pembelian Baju di Titik Kumpul Thrift Gunung Pangilun - Eva Rita Sonata (Universitas 45 Surabaya, 2024)
The purpose of this study is to determine the influence of segmentation, targeting and positioning on clothing purchasing decisions at the Gunung Pangilun thrift gathering point. This type of study uses quantitative methods, data collection through the distribution of questionnaires to 100 respondents using accidental sampling withdrawal techniques. By using instrument tests, (validity tests and reality tests), classical assumption tests (normality tests, multicollinearity tests and heteroschidasticity tests) then multiple linear regression and hypothesis tests with the help of SPSS applications. The result of this study is that segmentation has a positive and significant effect on purchasing decisions. Targeting (X2) has a positive and significant effect on Purchasing Decisions. Positioning (X3) has a positive and significant effect on Purchasing Decisions.